Appendiceal tumors and pseudomyxoma peritonei: French Intergroup Clinical Practice Guidelines for diagnosis, treatments and follow-up (RENAPE, RENAPATH, SNFGE, FFCD, GERCOR, UNICANCER, SFCD, SFED, SFRO, ACHBT, SFR). Issue 1 (January 2022) - Delhorme, Jean-Baptiste; Villeneuve, Laurent; Bouché, Olivier; Averous, Gerlinde; Dohan, Anthony; Gornet, Jean-Marc; You, Benoit; Bibeau, Frédéric; Dartigues, Peggy; Eveno, Clarisse; Fontaine, Juliette; Kepenekian, Vahan; et al.
Abstract: Introduction: This document is a summary of the French Intergroup guidelines regarding the management of appendicular epithelial tumors (AT) and pseudomyxoma peritonei (PMP) published in March 2020, available on the website of the French Society of Gastroenterology (SNFGE) (www.tncd.org ). Methods: All French medical societies specialized in the management of AT and PMP collaboratively established these recommendations based on literature until December 2019 and the results of a Delphi vote carried out by the Peritoneal Surface Oncology Group International experts, and graded into 4 categories (A, B, C, Expert Agreement) according to their level of evidence. Results: AT and PMP are rare but represent a wide range of clinico-pathological entities with several pathological classification systems and different biological behaviors. Their treatment modalities may vary accordingly and range from simple surveillance or laparoscopic appendectomy to complete cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC) and / or systemic chemotherapy. The prognosis of these neoplasms may also largely vary according to their pathological grade and spreading at diagnosis or during the follow-up. Given the rarity of certain situations, the therapeutic strategy adapted to each patient, must be discussed in a specialized multidisciplinary meeting after a specialized pathological and radiological pre-therapeutic assessment and a clinical examination by a surgeon specializing in the management of rare peritoneal malignancies. Conclusion: These recommendations are proposed to achieve the most beneficial strategy in a daily practice as the wide range and the rareness of these entities renders their management challenging. These guidelines are permanently being reviewed.